PENGGUNAAN METODE KOMPRESI TEKS UNTUK LAYANAN SMS OVER GPRS - Prijono, Wahyu Adi (SISTEM Jurnal Ilmu Ilmu Teknik, 2019)
The increasing number of short message service which has grown rapidly has bad impact towards its service quality. Delay in the system could increase while message delivered because the network gets burdened. Aplication Comresion text metode ( iD-Code companding algorithm) for predictive text has mode to reduce bits representation for each character. In the other hand by choosing new route like General Packet Radio Service (GPRS) will also significantly help to reduced burden of the network and also may achieve high rate of message delivery process. Based on analysis obtained that iD-Code Algorithm could truncates bit representation of predictive text file until 50% of value, with character average length only 4 bits. The implementation of iD-Code Algorithm also lead to the decreasing of packet holding time that also have impact reducing the packet delay time queue and further it will lead to the channel using efficiency.